2000
DOI: 10.2337/diacare.23.9.1227
|View full text |Cite
|
Sign up to set email alerts
|

Increased intake of calcium reverses vitamin B12 malabsorption induced by metformin.

Abstract: OBJECTIVE -Of patients who are prescribed metformin, 10-30% have evidence of reduced vitamin B 12 absorption. B 12 -intrinsic factor complex uptake by ileal cell surface receptors is known to be a process dependent on calcium availability. Metformin affects calciumdependent membrane action. The objective of this study was to determine the magnitude and mechanism of the reduction in serum vitamin B 12 after metformin administration. RESEARCH DESIGN AND METHODS-A comparative study design was employed using 2 gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
255
0
10

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 350 publications
(295 citation statements)
references
References 13 publications
8
255
0
10
Order By: Relevance
“…Metformin may also inhibit the calcium dependent absorption of the vitamin B 12 and intrinsic factor complex at the terminal ileum. This inhibitory effect could be reversed with calcium supplementation 22 .…”
Section: Clinical Studies Of Vitamin B 12 Deficiency In Indian Populamentioning
confidence: 99%
See 1 more Smart Citation
“…Metformin may also inhibit the calcium dependent absorption of the vitamin B 12 and intrinsic factor complex at the terminal ileum. This inhibitory effect could be reversed with calcium supplementation 22 .…”
Section: Clinical Studies Of Vitamin B 12 Deficiency In Indian Populamentioning
confidence: 99%
“…However, malabsorption of vitamin B 12 may not be easily diagnosed without close attention. Various studies have reported that an average of 10-30 % of patients taking metformin for longer duration and at higher dosage have shown vitamin B 12 deficiency [6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…It can also prevent vitamin B 12 deficiencies, which are common among T2DM patients treated with metformin [24]. It has also been shown that vitamin B 12 status can be improved by calcium supplementation [25], which was reported by only about 10% of the patients treated with metformin; this is unfortunate, given their very poor dietary calcium intake.…”
Section: Discussionmentioning
confidence: 83%
“…Dans le traitement par la metformine [10,26], le risque carentiel n'apparait que pour une dose moyenne de 2 g.j −1 et après une durée moyenne de traitement de 4 ans [80]. La metformine confère à la membrane des cellules pariétales de l'iléon une charge positive qui inhibe l'endocytose calciumdépendante du complexe vitamine B12-FI ; cette inhibition est réversible après un apport calcique [18].…”
Section: Malabsorption De La Vitamine B12unclassified